M. Kozybayev North Kazakhstan University - Mukhamejanova Г.Т.; Mukhamejanova А.Т. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The article considers the linguocultural character of expressive means. Expressive means are formed depending on the basic vocabulary of a nation in the literary language, the ability to use a word, on the development of oratory and the ability of the language of this nation to transmit information. Its specificity is due to the artistic perception of the surrounding world by the population, imaginative thinking, and its diversity. When determining the general nature of expressive means in the Kazakh language, the features of use and the reasons for use in a work of fiction (text, context), it is important and necessary to study the semantic structure, semantics, the combinative ability of each language unit in their composition, the semantic interpretation of the word, the meaningful semantic relations in the composition of the combination. Thus, it is possible to assess the level of linguistic and linguistic-cultural competence of the author of the text.